Psychological Impact of COVID-19 Pandemic Among the General Population in Jordan - Khatatbeh, Moawiah; Khasawneh, Aws; Hussein, Hasan; Altahat, Omar; Alhalaiqa, Fadwa (Frontiers in Psychiatry, 2021)
Objective: Pandemics are claimed to result in certain stressors. However, the potential psychological impact of a pandemic is often overlooked. The current study aimed to assess the psychological impact of the COVID-19 pandemic on Jordanians and to evaluate the influence of the socio-demographic variables on this impact. Method: The current study employed a descriptive cross-sectional design using the Impact of Event Scale—Revised (IES-R) via a web-based questionnaire. The researchers utilized convenience sampling which led to a total of 2,854 participants from the 12 governorates of Jordan. Results: The average score of the participants' responses on the IES-R questionnaire turned out to be 22.5 ± 11.7. Females were found to have more than double the odds of having an increased IES-R score [odds ratio (OR) = 2.2, confidence interval (CI) = 1.76–2.67] and participants who were older than 65 years had triple the odds of having the same risk compared to young adults aged 18–25 years (OR = 3.1, CI = 1.3–7.4). Significantly, having a family member diagnosed with COVID-19 placed individuals at a 7-fold higher risk of having an increased IRS-R score compared to their counterparts who did not have a family member diagnosed with COVID-19 (OR = 7, CI = 3.7–13.3). Conclusion: COVID-19 pandemic has imposed significant level of psychological burden on Jordanians, especially among females. Governments should collaborate with psychiatrists, mental health professionals and local institutions to offer high-quality, timely crisis-oriented psychological services to the affected individuals for the duration of the COVID-19 pandemic.